The Impact of Offshoring and Import Competition on Firm-Level Carbon Emissions - Jonathan Leisner; Jakob R. Munch; August Twile Nielsen; Georg Schaur (Institute of Labor Economics (IZA), 2023)
We use Danish firm-level data to examine the causal link between carbon emissions, offshoring, and import competition. Offshoring reduces firms' emission intensity but increases their production. Import competition reduces firms' production without affecting their emission intensity. For Denmark, these effects imply that observed offshoring trends reduced the overall manufacturing emission intensity while import competition did not. However, despite the emission reducing effects in local manufacturing, offshoring did not affect global emissions. Furthermore, import competition substantially increased global emissions. Therefore, based on offshoring and Chinese import competition, our results suggest that international trade may be bad for the global environment.
Keywords: F14; F18; Q54; Q56; 330; carbon emissions; offshoring; import competition